S100A4+ Macrophages Are Necessary for Pulmonary Fibrosis by Activating Lung Fibroblasts - Li, Yanan; Bao, Jing; Bian, Yangyang; Erben, Ulrike; Wang, Peigang; Song, Kun; Liu, Shuangqing; Li, Zhenzhen; Gao, Zhancheng; Qin, Zhihai (Frontiers in Immunology, 2018)
S100A4, a calcium-binding protein, can promote pulmonary fibrosis via fibroblast activation. Due partly to its various cellular origins, the exact role of S100A4 in the development of lung fibrosis remains elusive. Here, we show that in the bronchoalveolar lavage fluid, numbers of S100A4+ macrophages correlated well with S100A4 protein levels and occurrence of idiopathic pulmonary fibrosis (IPF) in patients. A mouse model of bleomycin-induced pulmonary fibrosis demonstrated S100A4+ macrophages as main source for extracellular S100A4 in the inflammatory phase. In vitro studies revealed that extracellular S100A4 could activate both mouse and human lung fibroblasts by upregulation of α-SMA and type I collagen, during which sphingosine-1-phosphate (S1P) increased. Inhibiting the S1P receptor subtypes S1P1/S1P3 abrogated fibroblast activation. Accordingly, absence or neutralization of S100A4 significantly attenuated bleomycin-induced lung fibrosis in vivo. Importantly, adoptive transfer of S100A4+ but not of S100A4- macrophages installed experimental lung injury in S100A4-/- mice that were otherwise not sensitive to fibrosis induction. Taken together, S100A4 released by macrophages promotes pulmonary fibrosis through activation of lung fibroblasts which is associated with S1P. This suggests that extracellular S100A4 or S100A4+ macrophages within the lung as promising targets for early clinical diagnosis or therapy of IPF.